Human-computer interaction as science - Reeves, Stuart (2015)
Human-computer interaction (HCI) has had a long and troublesome relationship to the role of 'science'. HCI's status as an academic object in terms of coherence and adequacy is often in question---leading to desires for establishing a true scientific discipline. In this paper I explore formative cognitive science influences on HCI, through the impact of early work on the design of input devices. The paper discusses a core idea that I argue has animated much HCI research since: the notion of scientific design spaces. In evaluating this concept, I disassemble the broader 'picture of science' in HCI and its role in constructing a disciplinary order for the increasingly diverse and overlapping research communities that contribute in some way to what we call 'HCI'. In concluding I explore notions of rigour and debates around how we might reassess HCI's disciplinarity.